Food facts & myths - Vallis, Adrian; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2000)
This program examines the food myths in the light of facts about food and nutrition, such as by eating plenty of bran, you can be assured of sufficient fibre, vitamin supplements are necessary for good health, you can eat as much fat as you like, provided that you exercise enough to burn it off, bread and potatoes cause you to put on weight, and chicken is better than red meat
Title from title screen
Executive producer, stephen Skok ; editor, Adrian Vallis ; camera, Sasha Trikojus, Adrian Vallis ; graphics, Chris Gallop, Adrian Vallis
Keywords: Food; Nutrition